Delirium researchers' perspectives of the challenges in delirium biomarker research: A qualitative study. - Ingrid Amgarth-Duff; Annmarie Hosie; Gideon A Caplan; Meera Agar (PLoS ONE)
Background Despite the prevalence and impact of delirium, its pathophysiology remains unclear. In order to advance this field of research, robust scientific methodology is required, yet quality of reporting in this field of research has been highly inconsistent. Delirium biomarker research poses several challenges, none of which have been documented in the literature before. The aim of this study was to explore the perspectives of delirium researchers about key methodological issues in delirium biomarker research. Methods Following a Delphi study with delirium experts resulting in 60 recommendations for reporting delirium biomarker studies, semi-structured interviews with international delirium researchers were conducted. Interviews were audio-taped and transcribed verbatim, followed by thematic analysis of the qualitative data. Results Fifteen participants were interviewed between August and November 2019. Most were male (n = 12; 75%), clinician researchers (n = 13; 86%), and had more than ten years' experience in conducting delirium research (n = 9; 60%). Analysis revealed two major themes and ten sub-themes, outlining key considerations to advance the field of delirium biomarker research. The major themes were: 1) Practical and scientific challenges of delirium biomarker research: stagnation versus driving improved methods and reporting; and 2) Valuing delirium research through investment and collaboration. Conclusion Findings identified a range of factors that contribute to the practical and ethical challenges of conducting delirium biomarker research, which have not previously been explicitly acknowledged or reported. A clear vision for collaborative efforts to enhance research quality for improved impact was also presented by the delirium researchers. This work complements the preceding Delphi and together these studies provide an in-depth understanding of what is needed in the field to inform and improve methods and reporting of delirium biomarker research.